Adverse Trends in Premature Cardiometabolic Mortality in the United States, 1999 to 2018 - Nilay S. Shah; Donald M. Lloyd‐Jones; Namratha R. Kandula; Mark D. Huffman; Simon Capewell; Martin O’Flaherty; Kiarri N. Kershaw; Mercedes R. Carnethon; Sadiya S. Khan (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background Life expectancy in the United States has recently declined, in part attributable to premature cardiometabolic mortality. We characterized national trends in premature cardiometabolic mortality, overall, and by race‐sex groups. Methods and Results Using death certificates from the Centers for Disease Control and Prevention's Wide‐Ranging Online Data for Epidemiologic Research, we quantified premature deaths (<65 years of age) from heart disease, cerebrovascular disease, and diabetes mellitus from 1999 to 2018. We calculated age‐adjusted mortality rates (AAMRs) and years of potential life lost (YPLL) from each cardiometabolic cause occurring at <65 years of age. We used Joinpoint regression to identify an inflection point in overall cardiometabolic AAMR trends. Average annual percent change in AAMRs and YPLL was quantified before and after the identified inflection point. From 1999 to 2018, annual premature deaths from heart disease (117 880 to 128 832), cerebrovascular disease (18 765 to 20 565), and diabetes mellitus (16 553 to 24 758) as an underlying cause of death increased. By 2018, 19.7% of all heart disease deaths, 13.9% of all cerebrovascular disease deaths, and 29.1% of all diabetes mellitus deaths were premature. AAMRs and YPLL from heart disease and cerebrovascular disease declined until the inflection point identified in 2011, then remained unchanged through 2018. Conversely, AAMRs and YPLL from diabetes mellitus did not change through 2011, then increased through 2018. Black men and women had higher AAMRs and greater YPLL for each cardiometabolic cause compared with White men and women, respectively. Conclusions Over one‐fifth of cardiometabolic deaths occurred at <65 years of age. Recent stagnation in cardiometabolic AAMRs and YPLL are compounded by persistent racial disparities.